Returning Home: Reducing Recidivism for Juvenile Offenders With Disabilities Through Transition Planning. (August 2018) - Miller, Alexandra A.; Therrien, William J.
Youth with disabilities are dramatically overrepresented in the juvenile justice system. These individuals have poorer outcomes compared with their nondisabled peers regarding school graduation, employment, and recidivism. This discussion article explores issues related to transition and outlines research-based practices aimed at increasing postrelease community engagement and decreasing the likelihood of rearrest. Three phases of transition are identified as well as key components, practices, and personnel that can guide transition from initial intake through reentry.